A Case for National History. Issue 1 (1st January 2003) - Samuel, Raphael
Abstract : The late and much lamented historian Raphael Samuel wrote this paper during the debate on the role of History as a national curriculum subject in England in the late 1980s. The Conservative government, under the lead of Kenneth Baker, the Minister for Education, introduced legislation for a National Curriculum that laid out in detail what was to be taught in English schools. History was one of the subjects in the magic circle; it turned out to be the most controversial, leading to an impassioned, adversarial debate reflecting the entrenched values and beliefs of the protagonists. Ralph Samuel, from a liberal perspective, in 1990 places this debate in its historical context, and uses it to suggest an alternative approach to a history curriculum that has 'nationalism' at its heart. Ralph's paper has a freshness, vitality and urgency that is as pertinent today as when it was written. In square brackets we have added explanatory notes.